THE USE OF CLUSTERING TECHNIQUE TO TEACH WRITING DESCRIPTIVE TEXT - Widiyanti, Fiki; Susilawati, Endang; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposes of this research are to investigate the significant difference between the pre-test and post-test of the writing descriptive text and to find out the effect size after being taught by using clustering technique of eighth grade students of SMPNegeri 21 Pontianak. The form of this research is a pre-experimental study with one group pre-test and post-test design. The sample of this research is class VIII G of SMP Negeri 21 Pontianak that consists of 37 students. The research findings show that the mean score of pre-test is 49,18 while the mean score of post-test is 76,10. It shows that clustering technique increases the students? writing skill. The result of t-test is 11,30. It is higher than t-critical value (11,30>2,042) in level of 0,05. As the result, the alternative hypothesis (Ha) is accepted. The calculation of effect size of the treatment is 1,9. It is categorized as ?High? based on the table of qualification of effect size as it indicates the result of 1,9 is higher than 0,8. It can be concluded that there is a highly significant effect of clustering technique to increase students? writing descriptive text on the eighth grade students of SMP Negeri 21 Pontianak.Keywords: Clustering Technique, Writing Skill, Descriptive Text